Development of E-Modules Based on Problem-Based Learning to Improve Problem-Solving Skills and Student Self-Efficacy - Hadira, Hadira; Sari, Murni Sapta; Sulisetijono, Sulisetijono (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
The purpose of this research was to develop and assess the validity, practicality, and effectiveness of an e-module on plant development using problem-based learning. The study was conducted at Universitas Negeri Malang, involving 63 third-semester biology students as research participants. The research employed the research and development approach, following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The validity test and practitioner evaluation were conducted by three expert faculty members, including a content expert, a media expert, and a practitioner expert. The effectiveness of the e-module was assessed through pretests and posttests, analyzing students' problem-solving skills and self-efficacy using ANCOVA. The media validity test revealed a score of 89.33% in the valid category, while the material experts scored 100% in the very valid category. The practitioner evaluation resulted in a score of 96.19% in the very practical category. The effectiveness test indicated significant values of 0.002 and 0.023 for problem-solving skills and self-efficacy, respectively, both of which were below the 0.05 significance level. This implies that there is a significant difference in the mean scores between the classes using problem-based e-modules and those employing problem-based learning without e-modules. Based on these findings, it can be concluded that the developed e-module is highly suitable as a learning resource for students.